Integrated digital twin and blockchain framework to support accountable information sharing in construction projects - Lee, Dongmin; Lee, Sang Hyun; Masoud, Neda; Krishnan, M.S.; Li, Victor C. (Automation in construction, 2021)
Efficient collaboration among various stakeholders is important for the successful completion of a construction project. However, stakeholders in construction are fragmented, which in turn hinders accountable information sharing. To address this issue, the authors aim to develop and test an integrated digital twin and blockchain framework for traceable data communication. The digital twin updates building information modeling in near real-time using internet of things sensors, while the blockchain authenticates and adds confidence to all data transactions to the digital twin. The authors tested the framework with a case project where virtual positioning data from a prefabricated brick is transmitted to digital twin in near real-time, recorded on the blockchain with time stamps. The results show that the integrated digital twin and blockchain framework makes all data transactions traceable. This paper's primary contribution is the development of a framework that realizes accountable project-related information sharing across stakeholders.